2004
DOI: 10.1007/s10238-004-0026-3
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid autoimmunity and dysfunction associated with type I interferon therapy

Abstract: Type I interferons are currently used for the treatment of chronic viral hepatitis, multiple sclerosis and several hematological and solid tumors. Side effects are not uncommon, and include multiple alterations in thyroid function, some of which are unrelated to autoimmunity. Review of the literature revealed an overall mean prevalence of incident thyroid dysfunction of 6.2%, hypothyroidism occurring more frequently (3.9%) than hyperthyroidism (2.3%). Destructive thyroiditis characterized by early transient th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 50 publications
2
48
0
3
Order By: Relevance
“…13,30,43 IFN␣ induced non-autoimmune thyroiditis exists in two forms, destructive thyroiditis and hypothyroidism.…”
Section: Non-autoimmune Interferon Induced Thyroiditismentioning
confidence: 99%
See 2 more Smart Citations
“…13,30,43 IFN␣ induced non-autoimmune thyroiditis exists in two forms, destructive thyroiditis and hypothyroidism.…”
Section: Non-autoimmune Interferon Induced Thyroiditismentioning
confidence: 99%
“…Indeed, several studies have shown patients infected with HCV are more susceptible to develop thyroid autoimmunity and interferon induce thyroiditis compared to patients infected with hepatitis B virus (HBV). 14,30,43,55 However, in these studies shorter regimens were being used to treat hepatitis B infection and it is possible that with the newer longer regimens the frequency of IIT in patients infected with HBV may be higher than originally reported.…”
Section: Non-genetic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Bir derlemede de, MS hastalarında anti-TPO pozitifliğinin %4-22 arasında olduğu belirtilmiştir. 22 Tiroid hormonları; beynin normal gelişimi, oligodendrosit matürasyonu ve miyelinizasyon için gereklidir. 23 Tiroid hormon eksikliğinin hipomiyelinizasyona yol açabildiği in vivo ortamda gösteril-miştir.…”
Section: Discussionunclassified
“…Levesque et al 1999;Alsalameh et al 1998], type I diabetes [Burdick et al 2009;Fabris et al 2003], and autoimmune hepatitis [Duchini, 2002;Heathcote, 1995]. Thyroid dysfunction is also a relatively common side effect of IFN treatment, particularly in patients with pre-existing thyroid autoimmunity [Monzani et al 2004]. As in the case of SLE, polymorphisms in the genes encoding proteins involved in the activation or activity of type I IFNs are also associated with a predisposition to develop certain of these diseases.…”
Section: Therapeutic Advances In Drug Safety 2 (3)mentioning
confidence: 99%